Motto ‘Tong Ngin Fan Ngin Jit Jong’ in Harmonization Life Public Malay and Chinese on Bangka Island - Damiasih Damiasih; Ropa Riana (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Culture and harmonization between two ethnic groups, namely Malay and Chinese on Bangka Island, are commonplace for local people on Bangka Island. The harmonization of the Malay and Chinese people of Bangka gave rise to the term "To Ngin Fan Ngin Jit Jong" which means that Chinese and Malays are the same. However, there are still local people who do not know the phrase local wisdom. This scientific article entitled "Preservation of Local Wisdom 'To Ngin Fan Ngin Jit Jong' in Harmonization of Malay and Chinese Community Life on Bangka Island", describes the answer to the problem formulation in the form of history from "To Ngin Fan Ngin Jit Jong" as well as efforts to preserve local wisdom "To Ngin Fan Ngin Jit Jong on Bangka Island. This lack of community knowledge about local wisdom supports the author in researching this scientific article. From the data that has been obtained and produces strategies or efforts in the preservation of local wisdom in order to introduce it to the public and tourists.